2023
DOI: 10.15252/embr.202357306
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 links lipid metabolism to contractile function of skeletal muscles

Abstract: Skeletal muscle plays a key role in systemic energy homeostasis besides its contractile function, but what links these functions is poorly defined. Protein Arginine Methyl Transferase 5 (PRMT5) is a well‐known oncoprotein but also expressed in healthy tissues with unclear physiological functions. As adult muscles express high levels of Prmt5, we generated skeletal muscle‐specific Prmt5 knockout (Prmt5MKO) mice. We observe reduced muscle mass, oxidative capacity, force production, and exercise performance in Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…PRMT5 has been shown to regulate lipid metabolism in adipocytes and skeletal muscles. 34 , 36 We have recently identified LD as an important metabolic regulator of SC fate, 14 we therefore explored whether PRMT5 regulates SCs through LDs. We utilized oil red O (ORO) staining to visualize and quantify LD contents in myoblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRMT5 has been shown to regulate lipid metabolism in adipocytes and skeletal muscles. 34 , 36 We have recently identified LD as an important metabolic regulator of SC fate, 14 we therefore explored whether PRMT5 regulates SCs through LDs. We utilized oil red O (ORO) staining to visualize and quantify LD contents in myoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, our recent study has demonstrated that myofiber-specific restoration of LDs rescues the phenotype of myofiber-specific Prmt5 -KO mice very effectively. 82 Future studies should explore the possibility of targeted delivery of HCQ into muscle cells using for example nanoparticle delivery tools. 83 , 84 …”
Section: Discussionmentioning
confidence: 99%